Analysis of Impoliteness Strategies in YouTube Comment Sections: A Case Study of Gibran Rakabuming's "Generasi Muda, Bonus Demografi, dan Masa depan Indonesia" - Sonya Pasaribu; Yolanda Marchella; Rifana Dwi Dywanti; Rahmad Ardiansyah; Meisuri Meisuri (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study investigates impoliteness strategies used in the YouTube comment section of Gibran Rakabuming's video entitled "Generasi Muda, Bonus Demografi, dan Masa Depan Indonesia." Using a qualitative approach and Culpeper's (2005) impoliteness framework, the researchers analyzed 50 purposively selected comments. The study identifies various strategies such as bald-on-record impoliteness, sarcasm/mock politeness, positive impoliteness, and negative impoliteness. The findings reveal that bald-on-record and sarcasm are the most frequent strategies used, often driven by political dissatisfaction and emotional expression. This study aims to determine the most dominant impoliteness strategy employed by netizens and contributes to understanding digital discourse in Indonesian political contexts, highlighting the role of anonymity and group identity in shaping online communication.